2017
DOI: 10.2528/pierc17051101
|View full text |Cite
|
Sign up to set email alerts
|

Bagley Power Divider With Uniform Transmission Lines for Arbitrary Power Ratio and Terminated in Different Impedances

Abstract: Abstract-This paper presents an unequal-split Bagley power divider that consists of uniform transmission lines and is terminated in different impedances. This divider should be only adjusted by altering the length of the transmission lines. Such alteration of the transmission lines will result in an arbitrary power ratio between output ports. The Bagley divider consists of uniform transmission lines of same characteristic impedance value despite different impedances for input and output port termination. For a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that, in [11,12], it seems that the value of K was chosen by trial-and-error, thus, a perfect match at the design frequency was not obtained. As a summary, the general design steps for a 3-way BPD with uniform TLs and a split ratio of P 2 : P 3 : P 4 are as follows:…”
Section: Design Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that, in [11,12], it seems that the value of K was chosen by trial-and-error, thus, a perfect match at the design frequency was not obtained. As a summary, the general design steps for a 3-way BPD with uniform TLs and a split ratio of P 2 : P 3 : P 4 are as follows:…”
Section: Design Equationsmentioning
confidence: 99%
“…However, the main drawback of the proposed design equations in the latter method is their inability to determine the exact value of the fixed characteristic impedance to obtain dividers with perfect input port matching at the design frequency. In [12], using the same approach, the authors of [11] proposed 3-and 5-way unequal-split BPDs using uniform TLs, and with output ports terminated in different impedances.…”
Section: Introductionmentioning
confidence: 99%
“…Although the technique is applied to a three-way Bagley divider with equal outputs, it can be extended to unequal Bagley power dividers like the one presented in [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…22 Some authors have also found that BPDs can be used for unequal output power splitting where, several techniques were reported in the literature to address this issue for 3-way BPD and 5-way BPD. [23][24][25][26][27] The main objective of this article is to investigate seven-way BPD with an arbitrary output power splitting for the first time. It would be of a special interest to extend the number of BPD output ports according to applications of these dividers in wireless communication systems, antenna feeders, radars, and RF amplifiers.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have improved designing BPDs by replacing microstrip lines with waveguides, 18,19 substrate integrated waveguide, 5,20,21 and coplanar waveguide 22 . Some authors have also found that BPDs can be used for unequal output power splitting where, several techniques were reported in the literature to address this issue for 3‐way BPD and 5‐way BPD 23‐27 …”
Section: Introductionmentioning
confidence: 99%